2018
DOI: 10.3389/fpsyt.2017.00260
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Internet-Based Guided Treatment for Genito-Pelvic Pain/Penetration Disorder: Rationale, Treatment Protocol, and Design of a Randomized Controlled Trial

Abstract: IntroductionGenito-pelvic pain/penetration disorder (GPPPD) not only adversely affects women’s sexuality and sexual satisfaction but is also associated with a wide range of psychosocial consequences such as reduced quality of life and well-being, mental health comorbidities, and relationship distress. Evidence for effective treatment options is scarce.AimThis article describes the rationale, treatment protocol, and study design for a randomized controlled trial examining the efficacy of an Internet-based guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 103 publications
0
10
0
Order By: Relevance
“…This diary can be accessed via a corresponding smartphone app. Both COPE and MIND have been developed based on existing face-to-face group treatments for low sexual desire (Brotto, Paterson, Basson, Driscoll, and Grabovac, unpublished data, 2015) as well as an internet-based intervention for women with genito-pelvic pain/penetration disorder [ 38 ]. If participants fail to log in to the platform for 7 consecutive days, they will receive up to 4 reminders (after 7, 14, 21, and approximately 30 days) by their eCoach and the study coordinator.…”
Section: Methodsmentioning
confidence: 99%
“…This diary can be accessed via a corresponding smartphone app. Both COPE and MIND have been developed based on existing face-to-face group treatments for low sexual desire (Brotto, Paterson, Basson, Driscoll, and Grabovac, unpublished data, 2015) as well as an internet-based intervention for women with genito-pelvic pain/penetration disorder [ 38 ]. If participants fail to log in to the platform for 7 consecutive days, they will receive up to 4 reminders (after 7, 14, 21, and approximately 30 days) by their eCoach and the study coordinator.…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of online interventions for sexual health has already been confirmed several times. For example, online interventions have focused on (1) various sexual problems and dysfunctions (Chisari et al, 2022;Jones & McCabe, 2011;Stephenson et al, 2021;van Lankveld, 2016;Van Lankveld et al, 2009;Weitkamp et al, 2021;Zarski et al, 2018;Zarski et al, 2017), (2) STIs (Carswell et al, 2012;Williamson et al, 2021), and (3) sex education (Martin et al, 2020;Mustanski et al, 2015;van Clief & Anemaat, 2020;Wadham et al, 2019). Online interventions offer many advantages: they allow easy access, are flexibly available, can be conducted anonymously, save time and travel, and are very cost-effective (Berger & Krieger, 2018;Buntrock et al, 2014;Ebert et al, 2018).…”
Section: Online Sexual Health Interventionsmentioning
confidence: 99%
“…There is paucity of evidence in favor of a specific management option for vaginismus 7, 8 and a recent (2018) meta-analysis concluded that women with vaginismus benefit from a range of treatments in majority of cases. 9 Multifaceted and interdisciplinary approach to painful sex disorders could lead to successful management outcomes (pain and intercourse).…”
Section: Management Of Vaginismusmentioning
confidence: 99%
“…6 Often, vaginismus comanifests with a wide range of concerns relating to general, relational, and psychosexual well-being. 7…”
Section: Introductionmentioning
confidence: 99%